Answer:
option C.
Explanation:
we have
System A
---> first equation system A
----> second equation system A
Multiply the second equation by 4 both sides
Adds this equation to the first equation system A
![-4x-4y=-12\\6x+y=2\\-----\\-4x+6x-4y+y=-12+2](https://img.qammunity.org/2020/formulas/mathematics/high-school/lvbxcwx9z6wyhvm7y931iws8puc61it8rg.png)
----> first equation system B
----> second equation system B
so
The first equation of System B is obtained by adding the first equation of System A to 4 times the second equation of System A
The second equations are identical
therefore
They will have the same solution